576. Continuing Disparities in Virologic Control for People Living with HIV (PLWH) Receiving Care at a Large, Urban, Safety-Net Clinic. (26th November 2018) - Lubelchek, Ronald; Diep, Lisa; Doshi, Kruti; Trick, William E; Adeyemi, Oluwatoyin
Abstract: Background: The National HIV/AIDS Strategy highlights reduction of HIV-related disparities as a key goal. Despite universal access to therapy in the United States, the CDC estimates that only 58% of PLWH have achieved virologic suppression. We carried out a recent analysis of virologic suppression, examining for associated factors for PLWH receiving care at one of the nation's largest, urban, safety-net clinics in order to identify ongoing outcome disparities. Methods: Ruth M. Rothstein CORE Center, Cook County Health and Hospital System's large, urban, safety-net HIV clinic cares for nearly 5, 000 PLHW in the Chicago area. We report rates of virologic suppression for PLWH who attended at least one primary care visit between March 31, 2017 and April 1, 2018. We assessed for associations between key demographic characteristics, inclusive of zip code of residence, and virologic suppression (VL < 200 copies/mL 3 ). Results: A total of 4, 660 patients attended at least one visit primary care visit at CORE between March 31, 2017 and April 1, 2018, of whom 84% were virologically suppressed. Sixty-six percent of our patients were African-American (AA), and 25% identified as Hispanic; 74% were male; patients' median age was 49. On multivariate analysis, AA race (OR 1.54, P = 0.006) correlated with ongoing viremia (VL > 200 copies/mL 3 ), while older age (age group 30 – 49, OR 0.62, P < 0.001; age group > 50 OR 0.27, P < 0.001) and identification as Hispanic (OR 0.63, P = 0.011) associated with virologic suppression. Other HIV transmission categories and demographic characteristics, inclusive of a health literacy measure, did not associate with virologic control. Of the Top 10 most populated zip codes of residence for our patients, three had a significantly higher proportion of viremic patients; while one had significantly more suppressed patients. Conclusion: Disparities in virologic suppression persist in younger and African-American PLWH who attended care at Chicago's largest, safety-net HIV clinic, with our data highlighting particular geographic areas of need. Structural interventions and quality improvement initiatives, at the health system and regional level, must continue to focus on improving outcomes for PLWH who fall into these demographic categories. Disclosures: R. Lubelchek, Viiv: Scientific Advisor, Salary.